2005
DOI: 10.1016/j.amjhyper.2005.06.013
|View full text |Cite
|
Sign up to set email alerts
|

True Resistant Hypertension: Is it Possible to Be Recognized in the Office?

Abstract: True RH can be recognized in the office in selected RH patients. We propose a simple scoring system with these variables that can be used in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 21 publications
4
93
1
2
Order By: Relevance
“…Overall, our cross-sectional study, in agreement with the findings of some (16,17) but not all investigators (14,15), demonstrates that nondipping is a common finding in patients with RH. The novel findings of our study are the extraordinarily high prevalence of nocturnal hypertension and the increased prevalence of nocturnal BP rising (and a trend toward less extreme dipping) in subjects with RH.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, our cross-sectional study, in agreement with the findings of some (16,17) but not all investigators (14,15), demonstrates that nondipping is a common finding in patients with RH. The novel findings of our study are the extraordinarily high prevalence of nocturnal hypertension and the increased prevalence of nocturnal BP rising (and a trend toward less extreme dipping) in subjects with RH.…”
Section: Discussionsupporting
confidence: 77%
“…In a study (22) of 62 healthy middle-aged men, the percentage fall in nocturnal mean arterial pressure was 15% and the proportion of nondippers was 13%. Using a standard definition of RH in a study of 313 such patients, Muxfeldt et al (17) found that the percentage fall in nocturnal systolic and diastolic BP was 7% and 10.5%, respectively, and the proportion of nondippers was 65.8%. However, 63% of the 184 white-coat resistant hypertensive patients in this study also had a nondipping pattern.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in line with the present study findings showing that despite the careful assessment of CBP in two study visits and after one pre-study visit more than one-third of subjects with CRH (36%) had low ABP (Figure 3). Another study by Muxfeldt et al 21 in 497 patients with RH in the clinic showed that those with elevated ABP (63%) had more severe target-organ damage (microalbuminuria and left ventricular hypertrophy) than those with low ABP. Redon et al 2 investigated the prognostic value of ABP compared with that of CBP in 86 subjects with RH in the clinic followed for 4 years and showed that subjects at the top tertile of ABP values had the worst cardiovascular prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…Resistant hypertension may also be secondary to other medical conditions, most often chronic kidney disease or primary hyperaldosteronism as well as renovascular disease and obstructive sleep apnea (7). Low potassium and target organ damage, including albuminuria, retinopathy and left ventricular hypertrophy, were more frequent in those found to have true resistant hypertension compared with those with white coat hypertension (8).…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%